2010
DOI: 10.1212/wnl.0b013e3181cff5d5
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic integrity underlies executive dysfunction in traumatic brain injury

Abstract: Objective: To quantify the effects of traumatic brain injury on integrity of thalamocortical projection fibers and to evaluate whether damage to these fibers accounts for impairments in executive function in chronic traumatic brain injury.Methods: High-resolution (voxel size: 0.78 mm ϫ 0.78 mm ϫ 3 mm 3 ) diffusion tensor MRI of the thalamus was conducted on 24 patients with a history of single, closed-head traumatic brain injury (TBI) (12 each of mild TBI and moderate to severe TBI) and 12 age-and education-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
154
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(171 citation statements)
references
References 31 publications
(20 reference statements)
11
154
0
5
Order By: Relevance
“…Supplemental 2 3 2 (group 3 time) ANCOVA analyses were also conducted to examine the effects of mTBI on voxel-wise subcortical diffusion metrics and vertex-wise cortical thickness measurements in light of previous results from patients with chronic mTBI. 3,4 However, no significant effects were detected for any analyses following appropriate corrections for false positives. Finally, a recent publication 25 identified significant longitudinal differences (within-subject) in regional brain volume over a 1-year period in patients with mTBI using paired t tests.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Supplemental 2 3 2 (group 3 time) ANCOVA analyses were also conducted to examine the effects of mTBI on voxel-wise subcortical diffusion metrics and vertex-wise cortical thickness measurements in light of previous results from patients with chronic mTBI. 3,4 However, no significant effects were detected for any analyses following appropriate corrections for false positives. Finally, a recent publication 25 identified significant longitudinal differences (within-subject) in regional brain volume over a 1-year period in patients with mTBI using paired t tests.…”
Section: Resultsmentioning
confidence: 90%
“…Previous studies reported nonsignificant trends 3 and reduced 4 anisotropic diffusion after mTBI. However, both studies were conducted with chronically symptomatic and/or mixed patient populations.…”
mentioning
confidence: 69%
“…20 Similarly, attempts to correlate structural injuries with postconcussive cognitive perfor- mance have shown mixed results without a strong anatomic/ pathologic correlation, with deficits detected in regions as diverse as the occipital cortex and corticospinal tracts. [21][22][23][24][25] This finding suggests that not all regions with differences in FA between patients and controls are necessarily symptomatic. 1 Reduced FA in 1 region alone may not, in and of itself, be clinically relevant.…”
Section: Discussionmentioning
confidence: 97%
“…Our study did not yield any correlations between CBF changes and memory and learning impairment, but poor performance in the Morris water maze was found to correlate with enhanced thalamic vessel density (r = -0.81, p < 0.01). The thalamus is often found to be damaged in moderate and severely injured TBI patients as well as in animal models (Pierce et al 1998, Maxwell et al 2004, Tollard et al 2009, Little et al 2010, but the role of the thalamic pathology in epileptogenesis after acquired etiologies like TBI is poorly understood (Bonilha et al 2004, Blumenfeld et al 2009). We also found that a high vessel density in the ipsilateral thalamus was associated with increased CBF and enhanced seizure susceptibility in injured rats.…”
Section: Correlation Of Mri Findings With Cognitive Deficits and Hypementioning
confidence: 99%